多発性肝転移に対し肝動注療法が奏効した胃扁平上皮癌の1症例 - 丸田 智章; 中村 茂樹; 島田 寛治; 金子 博; 畠山 勝義 (日本消化器外科学会雑誌, 2001)
多発性肝転移に対し肝動注療法が奏功した胃扁平上皮癌の1例を経験したので報告する. 症例は65歳の女性. 心高部不快感, 食欲不振で受診し, 胃癌および多発性肝転移と診断された. 1998年7月8日に胃全摘術および膵尾部, 膣合併切除と肝動注リザーバー留置が行われた. 組織診断で扁平上皮癌と診断された. pT2, sH1, sP0, PN2, cM0, Stage IVであった. 大彎リンパ節, 腹膣動脈周囲リンパ平上皮化が考えられた. 胃切除後肝転移に対して肝動注療法を施行し, CRと判定した. 新たな肝転移の出現や他部位への転移もなく術後2年9か月で健在である. We report a case of squamous cell carcinoma of stomach with multiple liver metastases. The patient was a 65-year-old woman with epigastralgia and appetite loss. Gastric cancer in the upper body of the stomach and multiple liver metastases were diagnosed. Total gastrectomy and perigastric lymph node dissection with caudal pancreatectomy and splenectomy were performed. Mitomycin C and fluorouracil were infused through the hepatic artery with a subcutaneous reservoir. The histological examination demonstrated squamous cell carcinoma. There was no evidence of adenocarcinoma in the main tumor. However, a few of the lymph node metastases showed adenocarcinoma. The pathogenesis of squamous cell carcinoma of the stomach might be squamous differentiation in a pre-existing adenocarcinoma. Liver metastases were reduced by hepatic arterial infusion. The patient is doing well 33 months after operation.